2011
DOI: 10.1002/jor.21385
|View full text |Cite
|
Sign up to set email alerts
|

Topical embryonic stem cells enhance wound healing in diabetic rats

Abstract: The effects of embryonic stem cells (ESCs) on diabetic wound healing were investigated using an excisional skin wound model in 110 diabetes-induced rats. We transplanted a clonal population of ESCs (5 Â 10 6 ) by topical injection into full thickness skin wounds. Four study groups were used; nondiabetic rats as a control, non-insulin controlled diabetic rats not treated with ESCs, insulin controlled diabetic rats not treated with ESCs, and insulin controlled diabetic rats treated with ESCs. Five rats in each e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 33 publications
3
46
0
Order By: Relevance
“…Previous studies reported that the MSCs migrate into the wound area [20] and differentiate into keratinocytes, endothelial cells, sweat glands, sebaceous glands and hair follicles [16,21,22]. Additionally, several studies have shown that MSCs secrete paracrine factors, such as VEGF, bFGF, epidermal growth factor, keratinocyte growth factor, insulin-like growth factor and hepatocyte growth factor [16,18,21,[23][24][25] and stimulate the deposition of extracellular matrix [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the MSCs migrate into the wound area [20] and differentiate into keratinocytes, endothelial cells, sweat glands, sebaceous glands and hair follicles [16,21,22]. Additionally, several studies have shown that MSCs secrete paracrine factors, such as VEGF, bFGF, epidermal growth factor, keratinocyte growth factor, insulin-like growth factor and hepatocyte growth factor [16,18,21,[23][24][25] and stimulate the deposition of extracellular matrix [26].…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells or progenitor cells seem to support this process by multiple paracrine effects especially by high levels of pro-angiogenic molecules (i.e., VEGF, HGF, bFGF, EGF, TGF-β, IGF-1) [44,45,46,47]. These effects could be demonstrated in rodent diabetic wounding models, further underscoring the significant activity of stem cells and their potential in repair-resistant chronic wounds [45,46,48,49]. …”
Section: Angiogenesis In Skin Wound Healingmentioning
confidence: 99%
“…Mouse skin wounding and stem cell implantation were performed as described previously (Lee et al, 2011;Kishibe et al, 2012). Briefly, after their backs had been shaved and treated with an organic iodine solution, a circular fullthickness wound was surgically created using an 8 mm diameter sterile biopsy punch.…”
Section: Mouse Skin Wound-healing Modelmentioning
confidence: 99%